Metabolic Engineering of Pseudomonas putida KT2440 for the Production of para-Hydroxy Benzoic Acid - Yu, Shiqin; Plan, Manuel R.; Winter, Gal; Krömer, Jens O. (Frontiers in Bioengineering and Biotechnology, 2016)
para-hydroxy benzoic acid (PHBA) is the key component for preparing parabens, a common preservatives in food, drugs and personal care products, as well as high performance bioplastics such as liquid crystal polymers (LCP). Pseudomonas putida KT2440 was engineered to produce PHBA from glucose via the shikimate pathway intermediate chorismate. To obtain the PHBA production strain, chorismate lyase UbiC from Escherichia coli and a feedback resistant 3-deoxy-D-arabino-heptulosonate-7-phosphate synthase encoded by gene aroGD146N were overexpressed individually and simultaneously. In addition, genes related to product degradation (pobA) or competing for the precursor chorismate (pheA and trpE) were deleted from the genome. To further improve PHBA production, the glucose metabolism repressor hexR was knocked out in order to increase erythrose-4- phosphate and NAPH supply. The best strain achieved a maximum titre of 1.73 g L-1 and a carbon yield of 18.1 % (C-mol C-mol-1) in a non-optimized fed-batch fermentation. This is to date the highest PHBA concentration produced by P. putida using a chorismate lyase.